Current Status of helicopter emergency medical services in China: A bibliometric analysis. Issue 6 (February 2019) - Xu, Ding; Luo, Peng; Li, Sheng; Pfeifer, Roman; Hildebrand, Frank; Pape, Hans-Christoph
Abstract: Background: After nearly 20 years of development, China has realized some achievements in helicopter emergency medical services (HEMS). The purpose of this article is to introduce and evaluate the development and characteristics of HEMS in China by collecting and analyzing relevant literature and, in so doing, help this vital service to further develop. Method: We conducted a Pubmed, Medline, Embase, ScienceDirect, Wanfang, CNKI, and VIP search of the literature on HEMS of China published between January 1950 and April 2017. The title, author name, number of authors, publishing date, country or region of origin, institution, type of article, study topic, funding source, and level of evidence of each article were recorded and analyzed. Results: There were 41 papers included in the analysis. All articles were published in Chinese. The selected articles were published between 2002 and 2017. The 41 articles originated from China, but 7 different regions were represented: East China (n = 14), followed by North China (n = 12), Central China (n = 8), Southwest China (n = 3), South China (n = 2), and Northwest China (n = 2). The articles included 18 clinical studies, 12 reviews, and 11 clinical guidelines. Among these, 22 articles were from public hospitals; 18 were from military units and 1 came from a private hospital. One article from the public hospitals was funded by public foundations (4.5%); 11 articles from the army units received support from Army funding (61.1%). Compared with the public and private hospitals, articles from military units were more likely to receive financial support (χ 2 = 15.7 P <.01). All the articles were assigned a level of evidence from 1 to 5. Level 5 (78.0%) was the most frequent level of evidence. There were 7 studies at level 4. Only 2 articles were assigned to level 3. There were no articles at levels 1 or 2. Conclusions: China's HEMS is a relatively new service. Its level of development is low, interregional development is uneven, and cooperation has been insufficient. We need to strengthen capital investment and develop a unified guideline to further enhance the development of HEMS in China.